The Correlation Between Transformational Leadership Style And Oorganizational Culture With Performance Of SESPIMMA POLRI'S Personnel In Jakarta - Charles Bohlen Purba; Supangat (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2016)
The purpose of this study is to analyze, test and determine: 1)The correlation between transformational leadership style with the Performance of SESPIMMA POLRI's Personnel in Jakarta. 2) The correlation between the organizational culture with the Performance of SESPIMMA POLRI's Personnel in Jakarta. 3) Relationship between both Transformational Leadership Style and Organizational Culture with the Performance of SESPIMMA POLRI's Personnel in Jakarta. This research was conducted in the South Jakarta area SESPIMMA Police Agency with the address of Jalan Ciputat Raya No. 40 Kebayoran Lama. The samples were gathered using the Slovin formula, then out of a total population of 131 people obtained a sample of 99 people. Data analysis was performed with SPSS versi17.0. Results of analysis can be concluded as follows: 1) There is a positive correlation between transformational leadership style with the Performance of SESPIMMA POLRI's Personnel in Jakarta, it can be determined by the calculation of the t-test where th> tt. Based on the calculation of the product-moment formula which, rh> rt. This means that the variations performed by SESPIMMA POLRI's Personnel (Variable Y) are determined by transformational leadership (X1 variable). 2) There is a positive relationship between the organizational culture and the performance of SESPIMMA Police personnel, it can be determined by the calculation of the t-test where th> tt. And based on the calculation of product-moment formula which, rh> rt. This means that the variations performed by SESPIMMA POLRI's Personnel (Variable Y) are determined by the Cultural Organization (Variable X2). 3) There is a positive relationship between Transformational Leadership and Organizational Culture with the performance of SESPIMMA POLRI's personnel, it can be determined by the calculation of the F test where Fh> Ft. And based on the calculation of product-moment it is known that rh>rt. This means that 48.9% of the variation Variable Y (Performance of SESPIMMA's Police Personnel) is determined by the Transformational Leadership (Variable X1) and Cultural Organization (Variable X2).